(untitled) (Texas Journal of Medical Science, 2023)
Cardiovascular disease (CVD) is the leading cause of morbidity and mortality worldwide [6]. They account for 31.5 percent of all deaths on the planet and 45 percent of deaths from non-communicable diseases, which is twice the death rate from cancer [7]. OCD is one of the most dangerous variants of IBD because it is the main nosological unit that causes death and disability among all cardiovascular diseases. Despite the positive changes achieved in recent years, the mortality rate from diseases of the circulatory system in our country and around the world remains high [12]. With the aging of the population, OCD becomes an increasingly common phenomenon